Swear Words in the Movie TED: A Sociolinguistics Study - Dyna Lidyawati; Ida Zuraida Supri (Jurnal Sinestesia, 2023)
This study examines swear words in the movie Ted and their purposes, focusing on sociolinguistic studies. Swear words are emotional words used in invective conversations, emphasizing the speaker's message. The study uses qualitative research methodology, examining the relationship between language and the context of its use. Swear words have specific power and can be shocking and effective when used in unexpected locations and contexts. The researcher uses the observation technique to analyze the swear words in the movie script. Data collected by watching the Ted movie on Netflix using observation techniques, studying the script, identifying swear words, categorizing the data, and examining the actors' intentions in the research produces propositions related to reasonable principles. The findings are then reviewed, grouped, and reported, resulting in a comprehensive study. The final results of the analysis were poured into the research. All of these classification categories were found in the movie. Then identifies five functions for swear words and suggests motives that influence swear words.